The Difference of The Achievement in English Speaking Abilities Between the Students in Front and Back Rows of Seating Position in The Classroom - Annisa, Nur (Journal Of Foreign Language Learning and Teaching, 2021)
Teaching is a profession that requires specialized skills and knowledge to impact significantly on student learning. One factor associated with improved achievement among learners is the position at which they sit in a classroom. This means that where students sit in the classroom may affect their academic achievement. Many researchers believe that students who sit in the front tend to have higher scores compared to the ones who sit in the back. Because teachers tend to direct more questions to students seated in the front rows of the classroom. Students seated at the back interact more with each other, in a disruptive way, thus minimizing their opportunity to learn. Educators should pay attention more to the classroom seating position of the students in order to perform highly estimated teaching learning process. Consequently, seating position may give significant difference in helping students to get good quality of teaching learning process.The aim of this research was to find out the significant difference of the ahievements between students that sit in front and back rows. This study was focused to find out the difference of the achievement in English speaking abilities towards 2016 and 2017 academic year students of English Department IAIN Palangka Raya.The method of this research was quantitave and ex post facto was the design of the research. The sample of the research was 2016 and 2017 academic year students of English Department at IAIN Palangka Raya consisting of 40 students taken by random sampling technique. The researcher used two kinds of instruments to collect the data of two variables. The instruments were questionnaire and speaking test. The first instrument was speaking test. Oral proficiency scoring categories from David P. Harris (1969) was used as guidance to measure students